Quality of Care and Outcomes of Inpatients with COPD: A Multi-Center Study in China - Wang F; Wang M; Chen X; Song A; Zeng H; Chen J; Wang L; Jiang W; Jiang M; Shi W; Li Y; Zhong H; et al. (International Journal of COPD)
Fengyan Wang,1,* Mingdie Wang,1,* Xiaoyan Chen,2,* Aiqi Song,3,* Hui Zeng,3 Jiawei Chen,3 Lingwei Wang,4 Wanyi Jiang,1 Mei Jiang,1 Weijuan Shi,1 Yuqi Li,1 Heng Zhong,5 Rongchang Chen,1,4,* Zhenyu Liang1,* 1State Key Laboratory of Respiratory Disease, National Clinical Research Center for Respiratory Disease, National Center for Respiratory Medicine, Guangzhou Institute of Respiratory Health, First Affiliated Hospital of Guangzhou Medical University, Guangzhou, 510120, People’s Republic of China; 2Foshan Fourth People’s Hospital, Foshan, 528000, People’s Republic of China; 3Guangzhou Medical University, Guangzhou, 510182, People’s Republic of China; 4Hetao Institute of Guangzhou National Laboratory, Shenzhen, 518000, People’s Republic of China; 5R&D China, AstraZeneca, Shanghai, 200040, People’s Republic of China*These authors contributed equally to this workCorrespondence: Zhenyu Liang, State Key Laboratory of Respiratory Disease, National Clinical Research Center for Respiratory Disease, National Center for Respiratory Medicine, Guangzhou Institute of Respiratory Health, First Affiliated Hospital of Guangzhou Medical University, Guangzhou, 510120, People’s Republic of China, Tel +86 13560157649, Email 490458234@qq.com Rongchang Chen, State Key Laboratory of Respiratory Disease, National Clinical Research Center for Respiratory Disease, National Center for Respiratory Medicine, Guangzhou Institute of Respiratory Health, First Affiliated Hospital of Guangzhou Medical University, Guangzhou, 510120, People’s Republic of China, Tel +86 13902273260, Email chenrc@vip.163.comObjective: Hospitalization due to chronic obstructive pulmonary disease (COPD) exacerbation is linked to worse prognosis and increased healthcare burden, especially in low- and middle-income countries. This study aimed to evaluate the quality of care and outcomes among inpatients with COPD and to identify prognostic factors relate to healthcare quality indicators.Methods: A multi-center, retrospective longitudinal study was conducted. Patients hospitalized for COPD exacerbations between January and December 2017 were randomly sampled from 16 secondary or tertiary public general hospitals in China. Healthcare quality process indicators and clinical outcomes were collected from medical records and patient questionnaires. The median follow-up period was 666 days. Multivariate logistic regression analysis was used to identify risk factors for readmission or death within 30 days after discharge and for one-year mortality.Results: A total of 891 inpatients with COPD were included. Among them, 14.3% underwent post-bronchodilator spirometry. Documentation of exacerbation history and symptom scores was found in 16.8% and 1.2% of medical records, respectively. Long-acting bronchodilators (LABDs) were prescribed at discharge in 30.3% of cases. Verbal counseling was the primary approach to smoking cessation education, rather than the 5A method. The 30-day readmission rate was 7.1%. The average exacerbation rate was 0.94 per patient during the following year, and the one-year mortality rate was 7.2%. Prescription of inhaled LABDs at discharge was significantly associated with a lower risk of readmission or death within 30 days (HR 0.51, 95% CI 0.29– 0.90, p=0.020). The presence of cardiovascular disease was associated with an increased risk of death within one year (HR 2.34, 95% CI 1.24– 4.41, p=0.002).Conclusion: The quality of inpatient care for COPD in China showed deficiencies in diagnostics, disease assessment, and patient education. Prescription of inhaled LABDs at discharge was a key quality measure that significantly reduced short-term readmission or mortality, highlighting its importance. Standardized protocols and clinician training are essential to improve patient outcomes.Keywords: chronic obstructive pulmonary disease, quality in health care, long-acting bronchodilators, patient readmission, prognosis